1996
DOI: 10.1111/j.1751-1097.1996.tb01834.x
|View full text |Cite
|
Sign up to set email alerts
|

A Photophysical Study of Purines and Theophylline by Using Laser‐Induced Optoacoustic Spectroscopy

Abstract: The photophysics of purinic compounds (purine, 6-methylpurine, 6-aminopurine [adenine], 6-chloropurine, 6-methoxypurine) and theophylline in acetonitrile solution were studied by pulsed laser-induced optoacoustic spectroscopy (LIOAS) exciting at 266 nm. The effect of O2, Xe and MnCl2 on the photophysical behavior of these compounds was studied; as well, the formation quantum yield of purine and 6-methylpurine triplet states were determined, with phi T = 0.88 +/- 0.03 for both compounds. Multiphotonic and deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Literature values only concern e T(max) of purine and pyrimidine nucleotides (AMP and GMP) which lie in the range 4 × 10 3 -1.3 × 10 4 M −1 cm −1 and appear to be higher for purine than for pyrimidine nucleotides. 25 By setting also a value of e T(max) = 10 4 M −1 cm −1 for 2ClPu, one obtains a U T value close to unity, which agrees with an earlier study of Murgida et al 26 for unsubstituted purine in aqueous solution (Table 1). Assuming similar e T(max) values for 6ClPu and 2,6diClPu, much lower values of triplet formation quantum yields close, to 0.1 were obtained for these two chloropurines (Table 1).…”
Section: Laser Photolysis Resultssupporting
confidence: 89%
“…Literature values only concern e T(max) of purine and pyrimidine nucleotides (AMP and GMP) which lie in the range 4 × 10 3 -1.3 × 10 4 M −1 cm −1 and appear to be higher for purine than for pyrimidine nucleotides. 25 By setting also a value of e T(max) = 10 4 M −1 cm −1 for 2ClPu, one obtains a U T value close to unity, which agrees with an earlier study of Murgida et al 26 for unsubstituted purine in aqueous solution (Table 1). Assuming similar e T(max) values for 6ClPu and 2,6diClPu, much lower values of triplet formation quantum yields close, to 0.1 were obtained for these two chloropurines (Table 1).…”
Section: Laser Photolysis Resultssupporting
confidence: 89%
“…132 Using similar methodologies, the triplet yield and the singlet oxygen quantum yield was also determined for tetraphenylporphyrin and its Zn and Cu complexes, 139 as well as for halogenated chlorins. 140 The photophysical properties of caffeine, theophylline, and theobromine, 141 and their benzophenone-photosensitized reactions in acetonitrile 38 were investigated by time-resolved LIOAS. In the three cases, global quenching rate constants of triplet benzophenone were measured as a function of temperature and it was observed that this is a non-activated process.…”
Section: Triplet States and Singlet Oxygen: Volume Changes And Quantu...mentioning
confidence: 99%
“…In previous papers we described the sensitized photooxidation of oxopurines (OP) (xanthines) by benzophenone, which take place by a type I mechanism via a hydrogen abstraction process (16) and different aspects of the photophysics of several purine derivatives (17)(18)(19). In the present work, we study the photosensitized oxidation of OP such as CF, TF, TB and 1,3,7-trimethyluric acid (TMU) (Scheme l), by RB.…”
Section: Introductionmentioning
confidence: 97%